MenschenAffen – AffenMenschen - Jacob, Frank (2022)
Monkeys are probably the animals with which we most readily identify when it comes to recognizing the human in the animal. Nevertheless, they symbolize, as it were, a fear of human degeneration. The particular human-animal relationship is the subject of this cultural history. Frank Jacob explains what role apes played for the self-perception of humans and how they were and are understood as humanoid animals, for example as objects in research and popular media. In doing so, he sheds light on a history of relationships that continues to this day, whereby the intensity of this relationship between humans and primates has been redefined again and again over the centuries.